The significance of portfolio assessment in EFL classroom - Rezqan Noor Farid (STKIP PGRI Banjarmasin, 2018)
The tendency of test maker and test developer in using conventional test items for students’ assessment fails the objective of the assessment itself since they do not represent activities students typically perform in classrooms. The alternative for this problem is portfolio assessment. Portfolio as a purposeful collection of students’ work that demonstrates their effort, progress, and achievements in given area can be used to measure the progress and achievement of students. This study is intended to reveal the significance of portfolio in assessing students’ achievements. This study is conducted using Ex Post Facto design with Causal Comparative approach. The research is conducted by choosing two classes of 10th grades in MAN 2 Martapura which used portfolio assessment and traditional assessment. The data are collected through observation and documentation consisting of number of the students, pre-test English score, and the score of final test. The result shows that the difference of assessment process the differences of student’s learning achievement between the two classes which use portfolio assessment and the class which use traditional assessment.